Harga-diri (Self-esteem)Terancam dan Perilaku Menghindar - Srisayekti, Wilis; Setiady, David A (Faculty of Psychology, Universitas Gadjah Mada, 2015)
This study concerned threatened self-esteem and prejudice that could appear in the form of behavior of avoiding minority groups. The hypothesis of this study was that participants whose self-esteem were threatened would show (1) avoidance behavior against any minority group target (i.e. Chinese group); and (2) less willingness to spend timeinteracting with them. This study involved 60 female students in Bandung, aged 18-20 years. They were Sundanese people, who belonged to the majority group. In this experimental study, they received feedbacks toward the results of intelligence tests, either positive or negative. Then, they were expected to interactwith the target group (Chinese) or with the majority group (Sundanese). The results confirmed the hypothesis 1, t(28) = 5.245p< .05; and did not confirm the hypothesis 2.